More sustainable electricity generation in hot and dry fuel cells with a novel hybrid membrane of Nafion/nano-silica/hydroxyl ionic liquid - Li, Yan; Shi, Yan; Mehio, Nada; Tan, Mingsheng; Wang, Zhiyong; Hu, Xiaohong; Chen, George Z.; Dai, Sheng; Jin, Xianbo (Elsevier, 2016)
A new hybrid proton exchange membrane (PEM) has been prepared from hydroxyl functionalized imidazolium ionic liquid (IL-OH), Nafion and nano-SiO2. The IL-OH, with a hydroxyl group that acts as both a proton acceptor and donor, forms strong hydrogen bonds with both Nafion and nano-SiO2, resulting in an effective hydrogen bond network in the ternary membrane. Such an anhydrous hydrogen-bond network, which is unknown previously, endows the PEMs with higher proton conductivity, greater thermal stability and surprisingly a more robust mechanical performance than PEMs consisting of conventional ionic liquids. The resulting PEMs have a tensile strength that is more than twice as strong as recast Nafion and an anhydrous ionic conductivity of ∼55 mS cm−1 at temperatures above 160 °C, with a proton transfer number of ∼0.9. A laboratory assembled H2–O2 fuel cell employing this new PEM delivered a power density of 340 and 420 mW cm−2 at 160 and 180 °C, respectively.